Nutraceuticals and amyloid neurodegenerative diseases: a focus on natural phenols. (January 2014) - Rigacci, Stefania; Stefani, Massimo
<x xml:space="preserve">Abstract</x> A common molecular feature of amyloid neurodegenerative diseases is the unfolding/misfolding of specific proteins/peptides which consequently become prone to aggregate into toxic assemblies and deposits that are the key histopathological trait of these pathologies. Apart from the rare early-onset familiar forms, these neurodegenerative diseases are age-associated disorders whose symptoms appear in aged people after long incubation periods. This makes the therapeutic approach particularly compelling and boosts the search for both early diagnostic tools and preventive approaches. In this last respect, natural compounds commonly present in foods and beverages are considered promising molecules, at least on the bench side. The so-called 'nutraceutical approach' suggests life-long healthy diets, particularly focusing on food molecules that are candidates to enter clinical trials as such or following a targeted molecular engineering. Natural phenols abundant in 'healthy' foods such as extra virgin olive oil, red wine, green tea, red berries and spices, appear particularly promising.